2013
DOI: 10.1016/j.bbagen.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Double-tailed lipid modification as a promising candidate for oligonucleotide delivery in mammalian cells

Abstract: Compared to the commercial lipoplex approach, oligodeoxyribonucleotide conjugation with C28 dual lipid modification seems to be promising to improve oligonucleotide delivery in mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…A recent study showed that double tailed, saturated lipid conjugated to an oligonucleotide significantly improved cellular uptake in a variety of tumor cell types (Ugarte-Uribe et al, 2013). Impressively, the conjugate significantly surpassed the cellular uptake achieved by transfection in HeLa cells.…”
Section: Lipid Conjugatesmentioning
confidence: 99%
“…A recent study showed that double tailed, saturated lipid conjugated to an oligonucleotide significantly improved cellular uptake in a variety of tumor cell types (Ugarte-Uribe et al, 2013). Impressively, the conjugate significantly surpassed the cellular uptake achieved by transfection in HeLa cells.…”
Section: Lipid Conjugatesmentioning
confidence: 99%
“…SPB preparation was performed as described previously. 23 Sucrose-enclosing GUVs were prepared using the electroformation method as described previously. 23 DOPC, DOPC/eSM/Chol (2:2:1) and eSM:Chol (2:1) stock solutions were prepared containing 0.4 mol% DiD (Invitrogen, Waltham, Massachusetts, USA).…”
Section: Spb and Guv Preparationmentioning
confidence: 99%
“…23 Sucrose-enclosing GUVs were prepared using the electroformation method as described previously. 23 DOPC, DOPC/eSM/Chol (2:2:1) and eSM:Chol (2:1) stock solutions were prepared containing 0.4 mol% DiD (Invitrogen, Waltham, Massachusetts, USA). Vesicles were generated in a 300 mM sucrose solution at 60ºC, a temperature rendering bilayers in a fluid phase state.…”
Section: Spb and Guv Preparationmentioning
confidence: 99%
See 2 more Smart Citations